A xylanase gene, xynA, has been cloned from thermophilic strain Geobacillus stearothermophilus, which was isolated from marine Tanjung Api, Indonesia. The polymerase chain reaction product of 1266 bp of xynA gene consisted of 1221 bp open reading frame and encoded 407 amino acids including 30 residues of signal peptide. The sequence exhibited highest identity of 98.7% in the level of amino acid, with an extracellular endo-1,4-β-xylanase from G. stearothermophilus T-6 (E-GSX T-6) of the glycoside - BUDI SAKSONO; LINDA SUKMARINI (HAYATI Journal of Biosciences, 2010)
A xylanase gene, xynA, has been cloned from thermophilic strain Geobacillus stearothermophilus, which was isolated from marine Tanjung Api, Indonesia. The polymerase chain reaction product of 1266 bp of xynA gene consisted of 1221 bp open reading frame and encoded 407 amino acids including 30 residues of signal peptide. The sequence exhibited highest identity of 98.7% in the level of amino acid, with an extracellular endo-1,4-β-xylanase from G. stearothermophilus T-6 (E-GSX T-6) of the glycoside hydrolase family 10 (GH10). A comparative study between the local strain G. stearothermophilus (GSX L) and E-GSX T-6 on homology of amino acid sequence indicated five differents amino acids in the gene. They were Threonine/Alanine (T/A), Asparagine/Aspartate (N/D), Lysine/Asparagine (K/N), Isoleucine/Methionine (I/M), Serine/Threonine (S/T) at the position 220, 227, 228, 233, and 245, respectively. Protein structural analysis of those differences suggested that those amino acids may play role in biochemical properties such as enzyme stability, in particular its thermostability.